Bone-specific alkaline phosphatase by immunoassay or electrophoresis: their use in clinical practice. Issue 3 (24th December 2014) - Ahmed, Farhan; Gibbons, Stephen M
Abstract : Background: Measurement of bone-specific alkaline phosphatase (BALP) may be useful in diagnosing and monitoring metabolic bone disease. This study aimed to evaluate the BALP immunoassay and compare it with electrophoresis (densitometry) for the quantitation of BALP. Methods: Metra BALP immunoassay kits were used for the method comparison. BALP was also quantitated by electrophoresis (densitometry) in seven patients with active Paget's disease. Results: Immunoassay results did not correlate well with densitometrically quantitated BALP, as there was a statistically significant (p<0.01), negative bias (22%) for results obtained by immunoassay compared with those derived by densitometry. Possible interference in the immunoassay with other isoforms of alkaline phosphatase (ALP) such as liver, placental and intestinal was also observed. The Metra BALP immunoassay is quoted as having an upper dynamic limit of 140 U/L and recommends that samples only require dilution above this level; we observed inconsistent results upon dilution of samples below this level. Conclusions: Immunoassay and electrophoresis did not correlate well for BALP quantitation. Possible interference with other isoforms of ALP was observed with the BALP immunoassay. The accuracy of the BALP immunoassay is questionable at higher concentrations.